Methodology of Care Humanitude in Promoting Self-care in Dependent People: An Integrative Review - Melo, Rosa Cândida de Carvalho Pereira de (2016)
Abstract. The aging of the population has led to an increase in the prevalence of chronic degenerative diseases and dependence. We need to implement humanized health care that will improve the quality of life and well-being of these people and help maintain their autonomy and self-care. Objective: To identify the implications of the caring in Humanitude in promoting self-care in the dependent person. Methods: Integrative review of the literature of the period between 2007 and 2015, using the databases Medline, EBSCO and Google Scholar. In using the PI[C]OD methodology and criteria for inclusion and exclusion, we obtained 54 items where 7 were selected for analysis. Results: There are several health benefits in the promotion of self-care, by ap-plying the Humanitude caring philosophy, mainly regarding the relationship be-tween the nurse and the patient. Conclusions: It is essential to develop further studies focused on the implications of caring in Humanitude in self-care in the dependent person.